Differential Trends in Health Care Utilization and Spending Among Asian American and Pacific Islander Medicare Beneficiaries before and During the COVID-19 Pandemic - Taylor Melanson; Tanvi Rao; Aditi Pathak; Mike Liu; Tracy Haidar; Rouguia Barry (Health Equity)
Introduction: The COVID-19 pandemic placed unprecedented strains on the U.S. health care system, contributing to significant disruptions of care. COVID-19 was also associated with an increase in negative sentiment toward and hate crimes targeting Asian Americans and Pacific Islanders (AAPI) individuals. The rise in anti-AAPI violence seen across the United States may have discouraged AAPI individuals from seeking medical care beyond the barriers to seeking care imposed on all persons by the pandemic. This study examines how COVID-19 and the concurrent increase in hate crimes targeting AAPI individuals impacted care utilization. Materials and Methods: We use fee-for-service claims from Medicare beneficiaries enrolled in Parts A and B for 2017–2021. We present descriptive results and use a difference-in-differences-style regression framework to estimate changes in ambulatory utilization associated with the COVID-19 pandemic and compare results across racial/ethnic groups. Results: The start of the pandemic is associated with decreases in the percentage of beneficiaries with ≥1 ambulatory visit, ambulatory visit rate, and ambulatory spending, among all racial/ethnic groups. AAPI beneficiaries suffer larger disruptions to all three measures of utilization, compared with other racial/ethnic groups. Discussion: Trends among AAPI beneficiaries are unlike those seen in Black, Hispanic, or White beneficiaries, suggesting that AAPI beneficiaries experience care disruptions different in cause and/or magnitude from the disruptions affecting other groups. Conclusions: Racial/ethnic disparities may be overlooked if results are only reported for some sub-groups. The experience of AAPI individuals during the COVID-19 pandemic is markedly different from that of other groups and warrants additional study.